Aggregation functions on bounded lattices. Issue 1 (2nd January 2017) - Karaçal, Funda; Mesiar, Radko
Abstract : In this paper, we show that the setA n ( L ) of all n -ary aggregation functions on a complete lattice L is a complete lattice and we study some properties of this lattice. If L is a bounded lattice and n is a natural number such thatn ≠ 0, we obtain thatL m form ∈ [ n ] can be embedded into the latticeA n ( L ) . We generate aggregation functions from monotone functions. We introduce the concept of internal product of aggregation functions. We give some examples of aggregation functions on bounded lattices.